Structure and electrostatic interaction properties of monolayers of amphiphilic molecules derived from C60-fullerenes: A film balance, neutron-, and infrared reflection study - Maierhofer, Andreas; Brettreich, Michael; Burghardt, Stephan; Vostrowsky, Otto; Hirsch, Andreas; Langridge, Sean; Bayerl, Thomas (Langmuir, 2000)
Monolayers at the air/water interface of a new amphiphilic molecule derived from a C-fullerene were studied at different lateral pressures by a combination of film balance techniques, neutron reflection (NR), and infrared reflection-absorption spectroscopy (IRRAS). The amphiphilic fullerene derivative (AF) consisted of a dendrimeric hydrophilic region, and 10 alkyl chains covalently attached to the fullerene cage formed the hydrophobic part. The AF monolayers could be compressed and expanded without significant hysteresis and the alkyl chains remained fluid at all pressures. By a titration series, the pK value of the AF monolayer was determined as 7.5 and pH dependent measurements allowed a variation of the negative AF headgroup charge by about 18 charges. The thickness of the AF monolayer at high lateral pressure was 30 angstroms, thus similar to that of typical phospholipid monolayers in the condensed state. In contrast, the AF molecular area was about 6-fold higher than that of phospholipids at high pressure. Moreover, the hydration capacity of the AF headgroup is significantly higher than that of phospholipids. The negatively charged AF monolayer showed a strong coupling of the water-soluble protein cytochrome c from the subphase, leading to the formation of a 30 angstroms thick protein layer underneath the AF layer. The protein content of this layer varied drastically with the pH value. The properties of the AF monolayers may be useful in the design of dedicated biomimetic surfaces.